Shifting self and system how educational leaders propel excellence for achieving equity - Ababio-Fernandez, Ruby; Winkfield, Courtney (Thousand Oaks, California Corwin, 2024)
Disrupting inequity is not a quick fix. The structural inequities that are deeply engrained our society have been perpetuated over the course of our country's history. Yet, history is also the present. We are now living in a moment of national reckoning around race and racism. How can we begin to move beyond buzzword rhetoric and "good intentions" to a place of action? All across the nation, whether by will, or pressure from external forces, countless school districts continue to make public declaration in service of creating more equitable systems for students in the wake of health, educational, racial pandemics unfolding in our country. And like most education buzz, the saturation of equity-focused initiatives has the potential to fade into oblivion without careful thought and intention. The proposed project is based on the professional experience and deep reflection of two leaders in the nation's largest school district leading the largest ever equity agenda. It is a response to a challenging question that resonates across all levels of our educational systems: "How do I lead this equity work?" Most seasoned education leaders have likely acquired tried-and-true strategies for approaching most challenges, but what if those go-to moves were the very thing standing in the way of real transformational change? What if our current times demand a new more radical leadership, one centered on interdependence? What if the challenge requires focus on not just performance but on harnessing the courageous efforts of self and others in an unyielding push for being, doing and showing up with fortitude and curiosity? What if our current challenge demands leaders who understand how to leverage will, empathy, resilience, understanding collective strength, capacity and heightened consciousness to lead through adaptive challenges that contribute substantially to a better humanity
Introduction -- Pillar One: The Journey -- Pillar Two: Adaptive Leadership -- Pillar Three: The Training Chase - Pitfalls and Possibilities of Equity Work -- Pillar Four: Emergence -- Pillar Five: Mastering Healing for a Better Humanity -- Epilogue.
Keywords: Discrimination in education -- United States; Racism in education -- United States; Multicultural education -- United States; Equality -- United States; Educational leadership -- United States